THE EFFECTIVENESS OF PARAPHRASING STRATEGY IN INCREASING UNIVERSITY STUDENTSâ READING COMPREHENSION AND WRITING ACHIEVEMENT - Hans, Diah Maulidya (Department of English Education of STAIN Jurai Siwo Metro, 2014)
Reading comprehension and writing as the crucial skills must be instructed effectively in order to engage the students in the meaningful teaching and learning process. One of the ways to increase studentsâ reading comprehension and writing achievement is by the use of paraphrasing strategy in the classroom instruction. Through the application of the paraphrasing strategy, it is easy for the students to internalize the information of the original source comprehensively; thus, studentsâ reading comprehension achievement is increased. In relation to the improvement of studentsâ reading comprehension achievement, studentsâ writing achievement is also increased by the use of paraphrasing strategy since the students can rewrite the text in to their own writing style. Therefore, the use of paraphrasing strategy is considered as one of the beneficial ways used to enhance studentsâ reading comprehension and writing achievement.